REVOLUTIONIZING ECTOPROSTHETICS IN PATIENTS WITH METACHRONIC AURICULAR TUMORS VIA 5D DIGITAL DESIGN - Kambarova Shakhnoza Alixuseynovna (KONFERENSIYALAR, 2025)
Annotation:Aesthetic, functional, and psychological illnesses are caused by defects of the craniofacial region of different etiologies, and these disorders are frequently only treated surgically using a variety of excision techniques. Regretfully, not all instances can be resolved surgically in terms of satisfactory cosmetic results or reconstructive treatments. Sometimes patients refuse major, multi-stage surgeries because of fear. Facial prosthesis is an alternate therapy option for patients in the scenarios mentioned. When manufacturing ectoprostheses, outstanding aesthetic outcomes are achievable because to modern silicone materials. These devices can be attached using medical adhesives, or the prosthesis can stick to the skin better thanks to the funnel-shaped structure.